Characterization of Kef Shfeir phosphate sludge (Gafsa, Tunisia) and optimization of its dewatering. (15th January 2020) - Ettoumi, M.; Jouini, M.; Neculita, C.M.; Bouhlel, S.; Coudert, L.; Haouech, I.; Benzaazoua, M.
Abstract: Water separation and recovery through thickening require adapted flocculants and densification processes. This study aimed to maximize water recovery from phosphate sludge (PS) at Kef Shfeir mine operation, Gafsa Phosphate Company, Tunisia. Representative samples of PS, PS treated with flocculant (F-PS), raw water, and recycled water were collected on the mine site. Solid samples (PS and F-PS) were characterized physically, chemically and mineralogically. To maximize water recovery, thickening tests were performed on the PS using different flocculants to optimize flocculant concentration, the agitation speed and the settling time. Results showed that PS had positive surface charge since its paste pH (7.3) was lower than pHPZC (8.0), whereas the tested flocculant (Slim Floc used by the company) showed negative surface charge. Solid samples contained coarse medium and fine particles of carbonates, silicates and residual hydroxyapatite. The cumulative fractions +32 μm of PS contained a promising residual potential of fluorapatite (up to 39.2%). Water recovery was about 58.1%, when the anionic Slim Floc was used, for a consumption rate of 1200 g/t of dry solids. Best efficiency (84%) of water recovery was obtained with the anionic flocculant E24 for a consumption rate of 360 g/t of dry solids, which is 3 times lower than actual flocculant consumption. Graphical abstract: Image 1 Highlights: Phosphate beneficiation processes consume high volumes of water. Phosphate processing produces large quantities of low density sludge. Phosphate sludge from sedimentary ores incorporates high amounts of residual P2 O5 . Phosphate sludge dewatering was optimized using flocculation process. Sludge densification with flocculants seems very promising for high water recovery.